Agent Environments for Multi-Agent Systems IV 4th International Workshop, E4MAS 2014 - 10 Years Later, Paris, France, May 6, 2014, Revised Selected and Invited Papers - Weyns, Danny; Michel, Fabien (Lecture Notes in Artificial Intelligence,, 2015)
This book constitutes the thoroughly refereed post-workshop proceedings of the 4th International Workshop on Environments for Multiagent Systems, E4MAS 2014 - 10 years later, held in Paris, France, in May 2014 as an associated event of AAMAS 2014, the 13th International Conference on Autonomous Agents and Multiagent Systems. The 6 revised full papers presented together with 1 roadmap paper and 7 invited papers were carefully reviewed and selected from 14 initial submissions. The papers are organized in topical sections on connecting agents, environments, and humans; environments for complex and stigmergic systems; virtual and simulated environments; and open agent environments and interoperability.